The impact of spectral filtration on image quality in micro‐CT system. (8th January 2016) - Ren, Liqiang; Ghani, Muhammad U; Wu, Di; Zheng, Bin; Chen, Yong; Yang, Kai; Wu, Xizeng; Liu, Hong
Abstract : This paper aims to evaluate the impact of spectral filtration on image quality in a microcomputed tomography (micro‐CT) system. A mouse phantom comprising 11 rods for modeling lung, muscle, adipose, and bones was scanned with 17 s and 2 min, respectively. The current (μA) for each scan was adjusted to achieve identical entrance exposure to the phantom, providing a baseline for image quality evaluation. For each region of interest (ROI) within specific composition, CT number variations, noise levels, and contrast‐to‐noise ratios (CNRs) were evaluated from the reconstructed images. CT number variations and CNRs for bone with high density, muscle, and adipose were compared with theoretical predictions. The results show that the impact of spectral filtration on image quality indicators, such as CNR in a micro‐CT system, is significantly associated with tissue characteristics. The findings may provide useful references for optimizing the scanning parameters of general micro‐CT systems in future imaging applications. PACS numbers: 87.57.C‐, 87.57.Q‐, 87.64.kd